Changes in organic carbon properties during intense plankton blooms and macroaggregate formation in the coastal Adriatic Sea, Croatia (case studies in 2020-2022) - SIMONOVIĆ, NIKI; MARGUŠ, MARIJA; PALIAGA, PAOLO; BUDIŠA, ANDREA; CIGLENEČKI, IRENA (Mediterranean Marine Science, 2024)
Organic matter (OM) properties, assessed with measurements of dissolved and particulate organic carbon (DOC and POC), surface-active DOC (SAS), and DOC normalized surfactant activity (NSA), have been under scrutiny during several recent and notable phenomena along the Adriatic Sea coast in Croatia. These phenomena were (1) massive invasive ctenophore blooms during the summer of 2020 and red tide occurrences in spring 2021 in the northern Adriatic, (2) the formation of the gelatinous macroaggregates in the coastal waters of the central Adriatic during the summer of 2021, and (3) intense autotrophic activity within the water column of the highly stratified and eutrophic marine system of Rogoznica Lake. All these events encompassed single-species plankton blooms characterized by a remarkable increase of OM (up to 320 mg L-1 of DOC and POC) with different surface-active properties (up to 15 mg L-1 of SAS) appearing in the otherwise oligotrophic Adriatic Sea. The NSA, in addition to voltammetric curves with well-defined desorption waves, is a good indicator of the presence of a different type of OM, which can be considered a possible tracer for certain processes in the marine environment. Based on our measurements, a rough threshold value for the OM hydrophobicity-reactivity of NSA = 0.083 is proposed. OM with a value above this threshold is more hydrophobic, as in the case of red tides and gelatinous zooplankton blooms with an average NSA between 0.13 and 0.16. OM with a value below this threshold indicates the presence of more hydrophilic substances such as pollen and OM produced by purple sulfur bacteria.